A Philippine newseum an exploratory study on the creation and audience reception of a Metro Manila-based news curation website - Layag, Sibyl Andrienne Naval (2012)
"This study explores the potential of establishing an independent local news website that curates and juxtaposes news from different online sources, aiming to create a more balanced reportage of current events and issues in a user-friendly online space. It will also assess the needed maintenance and sustainability of a news curation website in the current Filipino online media environment. The researchers conducted a survey to measure audience reception and focus interviews to determine the general attitude and overall knowledge of media practitioners with regard to the online medium, news aggregation and news curation. Based on the results of the study, there is needed a market for an independent local news curation website based in Metro Manila, as evidenced by the high ratings the proposed website garnered from the positive attitude of survey respondents towards news curation. In contrast, professional media practitioners generally regard this new development with a wary eye because of the constant tight competition online in terms of website traffic and advertising. However, most of them acknowledge the potential website's convenience, usefulness and the overall potential of the proposed endeavor."